The IT System of the Clearing House (ITSCH) – a new tool to combat tax frauds - Mariusz Macudziński (Prawo Budżetowe Państwa i Samorządu)
The presented publication is an attempt to analyse new tax law regulation – the electronic mechanism of network reporting: Communication System of Clearing House (Polish abbrev. STIR). This new reporting and analytical tool is designed for a more effective fight against tax crime by counteracting the use of the financial sector to tax frauds. The introduction of the STIR resulted in giving significant powers to the Head of the National Tax Administration and imposing new duties on financial institutions (banks, cooperative savings and credit unions as well as clearing house). The "risk analysis" and "bank account blocking" institutions deserve special attention. Firstly, they are key elements of the entire STIR mechanism. Secondly, these institutions have severe impact on the legal situation of the entities to which they are applied.